Managing the challenges of climate change mitigation and adaptation strategies in Ghana - Awuni, Stephen; Adarkwah, Francis; Ofori, Benjamin D; Purwestri, Ratna Chrismiari; Huertas Bernal, Diana Carolina; Hajek, Miroslav (Heliyon, 2023)
Ghana's economy is climate sensitive as more than 80% of its agricultural production is rainfall dependent, with only 2% of irrigation potential used. This has consequences under changing climate, with the impact projected to intensify if things go in a business-as-usual scenario. The manifestation of climate change impact is evident in other sectors of the economy, which requires proactiveness to adapt and mitigate through the development and execution of national adaptation strategies. This research reviews the impact of climate change and some interventions made toward its management. The study explored peer-reviewed journals, policy documents, and technical reports for relevant materials that chronicle programmes and measures to address the challenges of climate change. The research revealed that Ghana had experienced about 1 °C rise in temperature over the past four decades and sea level rise with socioeconomic consequences including decreased agricultural productivity and inundation of coastal communities. Policy interventions have resulted in the introduction of several mitigative and adaptation programmes, such as building resilience in various economic sectors. The study highlighted the progress and challenges to climate change implementation programmes and future policy implementation plans. Inadequate funding of programmes and projects was identified as a critical challenge to achieving climate change policy goals and objectives. We recommend more political will from the government and stakeholders towards policy implementation and greater commitment to providing adequate funding for programmes and project implementation to ensure the success of local climate action for adaptation and mitigation, as well as for sustainable development.
Keywords: Sustainable development; Mitigation; Climate change; Adaptation; Greenhouse gas; Ghana